Ethical issues in the early works of accounting - Garstka, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2019)
Accountants in Poland have recently had the opportunity to celebrate the 20th anniversary of the introduction of the Accounting Act. The act was passed by the Polish Parliament in 1994. 500 years earlier, a treaty on double-entry accounting system was published by Pacioli. The publishing of Tractatus XI. Particularis de computis et scripturis was a momentous event marking the beginning of a new field of economics. Double-entry accounting was in use since Cotrugli introduce it some thirty years before Pacioli published his work. Recently, in accounting as well as in economics, emphasis has been put on ethics, moral values, and professional attitudes. It is worth considering whether, or to what extent, these were present in the early works of accountancy from 550 years ago and how accountants approached these matters at the beginning of the written history of accounting. This article presents the main ideas included in the guidelines set by Pacioli and Cotrugli regarding double-entry systems and investigates if ethical guidelines were present there. It turns out that the author of an essential work in the history of accounting, as well as his predecessor, devoted much attention to the moral attitude of the merchant, their appropriate behaviour, their attitude towards customers, and their colleagues and competitors.